Pulsed Electron-Beam Melting of Cu-Steel 316 System: Evolution of Chemical Composition and Properties; 7 International conference on modification of materials with particle beams and plasma flows - Rotshtein V. P.; Markov A. B.; Ivanov Yu. F. Yuriy Fedorovich; Karlik K. V.; Uglov V. V. Vladimir Vasilievich; Kuleshov A. K.; Novitskaya M. V.; Dub S. N.; Pauleau Y.; Thièry F.; Shulepov I. A. Ivan Anisimovich (Modification of material properties, 2004)
Title from the title-page.